Khasiat Ekstrak Etanol Teh Hijau terhadap Pseudomonas aeruginosa - Fadila, Nahdiah Zahra (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2022)
Research about green tea ethanol extract efficacy against Pseudomonas aeruginosa has been finished. The green tea leaves were sourced from Agro Wonosari Tea Plantation, Malang Regency, East Java Province, Indonesia. Green tea leaves extract was obtained by maceration technique in which green tea leaves were soaked with ethanol 96% for 24 hours. After that, the filtrate was concentrated to be thick extract with no liquid content again.  After that, the concentrated extract was made by 5%, 10% and 15% as extract variations. The efficacy of green tea ethanol extract against Pseudomonas aeruginosa  was signed by increasing the inhibitory diameter that using disc method, in which the distilled water was used as negative blank. The results obtained for blanks, 5%, 10% and 15% extracts were 0; 1.85; 2.9 and 4.45 mm. The conclusion of this study is that the concentration of the extract is increasing proportionally to its inhibitory power, the higher of extract concentration is higher of its inhibitory activity against Pseudomonas aeruginosa. The conclusion described the green tea ethanol extract was effective to be antibacterial agent against Pseudomonas aeruginosa.